TINJAUAN YURIDIS TINDAK PIDANA PENYEBARAN KONTEN PORNOGRAFI DENGAN MOTIF BALAS DENDAM - Gultom, David Kristo Gultom; Hendri Jayadi; Poltak Siringoringo (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Online crime, or cybercrime, has become a new trend in many countries, including Indonesia. Among the online crimes that have spread recently is pornography with the motive of revenge, but there are still many people who do not understand the motive for this crime. This is because the public is not aware of the importance of understanding that this is a crime. The formulation of the problem in this thesis is whether pornography with the motive of revenge is included in the criminal act of spreading pornography or not, and what are the judges' considerations in passing a decision on the perpetrators of spreading revenge pornography in Decision Number XX/XXXX/XXXX/XXXX. This research is normative legal research with statutory and case approaches. The data used is from the Penal Code, the Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions (ITE), the Law of the Republic of Indonesia Number 44 of 2008 concerning Pornography, the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning ITE, and the Law Number 12 of 2022 concerning Crimes of Sexual Violence, while secondary legal materials were obtained from books and other literature, and tertiary legal materials such as legal dictionaries, language dictionaries, and legal encyclopedias. From the results of this study, it can be concluded that Based on the motive of vengeance and the judge's considerations in Decision No. XX/XXXX/XXXX/XXXX is not appropriate because there are legal facts that were revealed but were set aside by the Panel of Judges so that in their considerations they directly applied the Pornography Law without considering the ITE Law as charged by the Public Prosecutor in the second Prosecutor in the second Prosecutor in the second Prosecutor in the indictment